PENGARUH ELEVASI POSISI KEPALA PADA KLIEN STROKE HEMORAGIK TERHADAD TEKANAN RATA-RATA ARTERIAL, TEKANAN DARAH DAN TEKANAN INTRA KRANIAL DI RUMAH SAKIT MARGONO SOEKARJO PURWOKERTO TAHUN 2011 - Supadi, Supadi (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2012)
Abstract Stroke result in mortality cases in the developing countries such as Indonesia. Indonesia Healthcare Ministry reported that stroke was the first rank of death fatality among hospitalized patients. The disease also has been founded in many countries. Annual published statistics at The Margono Soekarjo Hospital Purwokerto indicated that stroke revealed top ten cases in neurologic department. The incidence of stroke showed steadily increased since 2007. The aim of the study was to investigate the effect of head elevation on mean arterial pressure, blood pressure, and intracranial pressure among hemorrhagic stroke at the Margono Soekarjo Hospital Purwokerto on 2011.The study was employed quasi experimental design pre and post test with control group. This research used analytical descriptive. And, the data was analyzed by t test dependent and chi square analysis approach. There was significant effect of head elevation positioning on mean arterial pressure, blood pressure, and intracranial pressure among hemorrhagic stroke patients after the treatment (p value 0, 00) of intervention group in the Margono Soekarjo Hospital Purwokerto. Meanwhile, there was no significant change of control group on mean arterial pressure, systolic and diastolic blood pressure, and intracranial pressure (p values were 0,206, 0,761 and 0,092, and 0,058 respectively). The study showed that there was significant effect of head elevation positioning on mean arterial pressure, blood pressure, and intracranial pressure among hemorrhagic stroke patients after the treatment (p value 0, 00). Keywords: head elevation, intracranial pressure, blood pressure, MAP, hemorrhagic stroke   Kesmasindo. Volume 5,  Nomor 2,  Juli  2012,  hlm. 154- 168